Empirical estimates and theoretical predictions of the shorting factor for the THEMIS double‐probe electric field instrument. Issue 7 (4th July 2016) - Califf, S.; Cully, C. M.
Abstract: Double‐probe electric field measurements on board spacecraft present significant technical challenges, especially in the inner magnetosphere where the ambient plasma characteristics can vary dramatically and alter the behavior of the instrument. We explore the shorting factor for the Time History of Events and Macroscale Interactions during Substorms electric field instrument, which is a scale factor error on the measured electric field due to coupling between the sensing spheres and the long wire booms, using both an empirical technique and through simulations with varying levels of fidelity. The empirical data and simulations both show that there is effectively no shorting when the spacecraft is immersed in high‐density plasma deep within the plasmasphere and that shorting becomes more prominent as plasma density decreases and the Debye length increases outside the plasmasphere. However, there is a significant discrepancy between the data and theory for the shorting factor in low‐density plasmas: the empirical estimate indicates 0.7 shorting for long Debye lengths, but the simulations predict a shorting factor of 0.94. This paper systematically steps through the empirical and modeling methods leading to the disagreement with the intention of motivating further study on the topic. Key Points: The double‐probe shorting factor is variable in the inner magnetosphere There is effectively no shorting in high‐density plasmas, and the shorting factor approaches a limit for vacuum as density decreases Experimental estimates suggest 0.7 shorting in low densities for THEMIS, but theory predicts 0.94